О значениях и функции модальных глаголов при предикатах зрительного восприятия в английском языке - Усонене, Аурелия (Kalbotyra, 1983)
The meaning of the predicates CAN/COULD + a verb of sense perception has been the object of considerable argument among linguists. It is generally assumed that the auxiliary CAN in such cases “loses its modal value” and functions as a marker of progressive aspect or denotes a state. We share the alternative view according to which the presence of CAN/COULD is always meaningful and it conveys some additional information. An attempt has been made to establish a distinction between the utterances containing CAN/COULD SEE that express (1) potential ability/possibility of visual perception and (2) actualized (realization of) ability or possibility of visual perception. It is to be noted that this serves as an additional proof that SEE is not stative.